Family Support with Adolescent Smoking Behavior in High School - Widagdo, Wahyu; Basuki, Pralamphita Afifah (Asian Journal of Pharmaceutical Research and Development, 2022)
Adolescents are residents with an age range of 10-18 years. At this stage of adolescence, adolescents are still looking for their identity so they need guidance and support from their families. The family support provided can influence the behavior of adolescents and shape adolescents for the better. In adolescents, health problems often occur, one of which is smoking so that the number of adolescents who smoke in Indonesia has increased from 2013 with a prevalence of 7.20% to 9.10% in 2018. Meanwhile, the prevalence in DKI Jakarta Province is adolescents aged 10-18 years by 4.51%. Therefore, it is important to know whether or not there is a relationship between family support and smoking behavior. This study used a cross sectional design with a sample of 116 adolescents. Data were collected using a questionnaire. The results of this study there is no relationship between family support and smoking behavior in adolescents at senior high schools in DKI Jakarta province with value = 0.267, value = 0.05 (ρ> ).